Epidemiology of Respiratory Syncytial Virus–related Hospitalizations and the Influence of Viral Coinfections in Southern Austria in a 7-year Period. Issue 1 (January 2020) - Resch, Bernhard; Puchas, Claudia; Resch, Elisabeth; Urlesberger, Berndt
Abstract : Objective: The aim of this study was to determine the respiratory syncytial virus (RSV) epidemiology and to analyze the influence of risk factors and coinfections over the last years. Methods: Retrospectively all infants, children and adolescents hospitalized due to respiratory disease with positive RSV test [hospitalized for RSV infection (RSV-H)] between January 1, 2009, and December 31, 2015, at a tertiary care center in the southern part of Austria were included for analysis. Patients were all identified by a search via International Classification of Diseases and Related Health Problems, 10th Edition codes, and all medical data were collected from the local electronic databases called openMedocs. RSV tests had to prove true infection case definition. Results: During a 7-year study period, 745 infants, children and adolescents exhibited RSV-H. Main diagnosis was bronchiolitis (70%). Nearly half of all cases (44%) were born during the first half of the RSV season (November–January), and seasonal peak of RSV-H was in January. Predominant underlying condition was history of prematurity in 15% followed by neurologic impairment (3.5%) and hemodynamically significant congenital heart disease (2.95%). Age ⩽2 months and underlying conditions/morbidities were associated with more severe disease. The majority of cases (96%) had an age below 24 months, and 91% below 12 months. Viral coinfection (most common influenza virus, adenovirus and rhinovirus) was diagnosed in 37 cases (5%) resulting in a more severe course of disease. Main risk factors of coinfection were siblings and crowding. Mortality was 0.27% (2/745). Both children had coinfection with influenza A virus and were multihandicapped (15 and 20 years of age, respectively). Conclusions: Prematurity and underlying morbidities play a marked role in RSV-H. Viral coinfections aggravated disease with death in 2 multihandicapped adolescents.